2011
DOI: 10.2147/ijn.s13267
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental pulp stones and calcifying nanoparticles

Abstract: The etiology of dental pulp stones, one type of extraskeletal calcification disease, remains elusive to date. Calcifying nanoparticles (CNPs), formerly referred to as nanobacteria, were reported to be one etiological factor in a number of extraskeletal calcification diseases. We hypothesized that CNPs are involved in the calcification of the dental pulp tissue, and therefore investigated the link between CNPs and dental pulp stones. Sixty-five freshly collected dental pulp stones, each from a different patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A strong correlation between the chronicity of the renal disease and the pulp narrowing has been observed in the premolar and molar teeth of such patients ( 12 ). A number of studies have suggested that pulp stones results as a manifestation of systemic illnesses leading to pathological biomineralization in many parts of the body ( 13 , 14 ). Few others have suggested that the complex biomechanical and physiologic changes occurring in these systemic diseases do not affect the dentin and pulp, stating that no such correlation exists ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between the chronicity of the renal disease and the pulp narrowing has been observed in the premolar and molar teeth of such patients ( 12 ). A number of studies have suggested that pulp stones results as a manifestation of systemic illnesses leading to pathological biomineralization in many parts of the body ( 13 , 14 ). Few others have suggested that the complex biomechanical and physiologic changes occurring in these systemic diseases do not affect the dentin and pulp, stating that no such correlation exists ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6] A recent study focus the relationship of dental pulp calcification and nanoparticle and nanobacteria, but it is insufficient to tell about the exact etiology. [7] A few studies have shown the link between dental pulp stone and prevalence of kidney stone, and some others in relation to carotid calcification. [89] Here, in our study, we have tried to collect the data from the calcification in subjects where the causes were seldom found.…”
Section: Introductionmentioning
confidence: 99%
“…Such event becomes a leading cause for ischemic heart disease causing significant mortality and morbidity [ 12 ]. According to other theory, calcifying nanoparticles classified nanobacteria’s are the key factors for the pathological calcifications seen in the gall stones, joint calcification, renal calculi, atherosclerotic plaque and PS [ 12 , 25 ]. In the recent past, osteopontin, a new component of atherosclerotic plaques, was reported to play a role in plaque calcification [ 13 ].…”
Section: Discussionmentioning
confidence: 99%